2013
DOI: 10.23986/afsci.6699
|View full text |Cite
|
Sign up to set email alerts
|

Silage and the safety and quality of dairy foods: a review

Abstract: Silage contains a number of potential hazards to the safety and quality of milk and dairy products. This paper reviews the present knowledge about silage as a source of (1) spores of anaerobic spore-formers (Clostridium species) and aerobic spore-formers (mainly Bacillus and Paenibacillus species), (2) the zoonotic pathogenic bacteria Listeria monocytogenes and Escherichia coli, and (3) mycotoxins. A distinction is made between field-derived mycotoxins, i.e. mycotoxins that are formed during growth of crops in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 94 publications
7
119
0
6
Order By: Relevance
“…Indeed, while for cow's milk, high clostridial spore counts are mainly recorded in winter, due to silage feeding (Driehuis 2013;Zucali et al 2015), for ewe's milk, high MPN counts have also been observed in summer. This could be due to environmental factors, husbandry and feeding practices other than silage feeding, such as wool spore contamination, milking hygiene, and an incorrect management of the bedding, especially during anomalous summer seasons (i.e., particularly rainy or dry).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while for cow's milk, high clostridial spore counts are mainly recorded in winter, due to silage feeding (Driehuis 2013;Zucali et al 2015), for ewe's milk, high MPN counts have also been observed in summer. This could be due to environmental factors, husbandry and feeding practices other than silage feeding, such as wool spore contamination, milking hygiene, and an incorrect management of the bedding, especially during anomalous summer seasons (i.e., particularly rainy or dry).…”
Section: Discussionmentioning
confidence: 99%
“…Slug contamination of crops gave a severe negative effect on the microbiological quality of silage by increasing C. tyrobutyricum known to decrease nutritional value and palatability (Driehuis, 2013). Although no pathogens were detected after strictly anaerobic fermentation, the pH was above the critical level of microbial inhibition (pH 4.2) with increasing slug level for both low and high DM silages (Tables 2 and 3).…”
Section: Microbiological Quality Of Slug Contaminated Silagementioning
confidence: 98%
“…Silage is considered the main source of butyric acid bacteria (BAB) contamination of milk, where even low levels of BAB are sufficient to spoil semi-hard cheeses (Vissers et al, 2006;Driehuis, 2013). Contamination levels of silage below 3 log 10 BAB/g would provide high quality milk, given a basic pretreatment of the udder teats before milking.…”
Section: Tyrobutyricum Levels and Risk Of Milk Contaminationmentioning
confidence: 99%
See 2 more Smart Citations